Intervensi Pendidikan Kesehatan terhadap Perubahan Pengetahuan mengenai Kejadian Dermatitis dan Pencegahannya di Desa Pantai Cermin Kanan Kecamatan Pantai Cermin Kabupaten Serdang Bedagai - Annisa Febriana Siregar; Anggi Isnani Parinduri (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2020)
Fishermen are prone to skin diseases due to the influence of sea water because the concentration of salt draws water from the skin. Sea water is a cause of dermatitis with primary stimulation properties. Recent research results reveal that fishermen have a high potential for disease, work accidents, and mental health and other physical-related illnesses. The purpose of this study was to determine the effect of leaflet and extension media on changes in knowledge about the incidence of dermatitis between before and after counseling to fishermen in Pantai Cermin Kanan Village, Pantai District in 2020. The design of this research is a non-equivalent control group design study. Nonequivalent Control Group Design is a form of Quasi-Experimental. The research population was 50 fishermen in Pantai Cermin Kanan District. The data collection method uses primary data, namely data that is directly obtained from respondents using a questionnaire in the form of a statement or written question. The data analysis used in this study consisted of univariate and bivariate analyzes. This analysis uses descriptive statistics to describe the frequency distribution of the independent and dependent variables which are presented in tabular form. The bivariate analysis used in this study was the Paired Sample T-test. There is a difference in the knowledge of fishermen in Pantai Cermin Kanan Village regarding the use of good PPE between before and after a health education intervention regarding the potential dangers of dermatitis and its prevention.